Fabrication of Quasi-2D Shape-Tailored Microparticles using Wettability Contrast-Based Platforms - Neto, Mafalda D.; Stoppa, Aukha; Neto, Miguel A.; Oliveira, Filipe J.; Gomes, Maria C.; Boccaccini, Aldo R.; Levkin, Pavel A.; Oliveira, Mariana B.; Mano, Joao F. (Advanced Materials, 2021)
The ability to fabricate materials with ultrathin architectures enables the breakthrough of low-dimensional structures with high surface area that showcase distinctive properties from their bulk counterparts. They are exploited in a wide range of fields, including energy harvesting, catalysis, and biomedicine. Despite such versatility, the fine tuning of the lateral dimensions and geometry of these structures remains challenging. Prepatterned platforms gain significant attention as enabling technologies to process materials with highly controlled shapes and dimensions. Herein, different nanometer-thick particles of various lateral sizes and geometries (e.g., squares, circles, triangles, hexagons) are processed with high precision and definition, taking advantage of the wettability contrast of oleophilic-oleophobic patterned surfaces. Quasi-2D polymeric microparticles with high shape- and size-fidelity can be retrieved as freestanding objects in a single step. These structures show cell-mediated pliability, and their integration in gravity-enforced human adipose-derived stem cell spheroids leads to an enhanced metabolic activity and a modulated secretion of proangiogenic factors.
CRIS-Team WoS Importer:2021-03-12